Public Participation in Reforestation (Case at Gunungkidul Regency, Yogyakarta Special Province) - Ritohardoyo, Su; Prakosa, B S (Forum Geografi, 2002)
Popular participation is a determinant indicator of reforestation. The important of it is due to the fact, that the people who will take the conservation innovation, adopt the technology, and bear the impact of conservation. However, there are many cases indicate the failure of reforestation project because of low popular participation. In this regard, this research is conducted to expose spatially the people knowledge, perception, and participation on reforestation. This research is carried out in the Gunungkidul district employing survey method primary data is collected from 180 rspondents are households who as participant of reforestation project, and household who are classified as self sufficient. The respondent sample is selected on the basis of stratified random sampling, according to physiography and the existing of forestation programme of the area. Three villages sample selected in this research are 1) Tegalrejo, in the physiography of Baturagung Range; 2) Gedangrejo, in the physiography of Wonosari Plateau; 3) Banjarejo, in the physiography of Gunungsewu Mountain. The measurement of people knowledge, perception, and participation on reforestation is performed through Likert Scale technique. Data analysis makes use of tabulation statistic technique espeially t test, variance, and rank correlation.The result of research shows that most people gain the reforestation knowledge from Foresty Extension Service or RLKT, whereas the knowledge of the larger part of self sufficient household comes from village officers. Though the category of their degree of knowledge are high, however there are quiet different according to physiography area. This fact determines the level of popular participation in the perspective physiography unit. It means that the higher the degree of knowledge on reforestation leads to the higher the perception on forestation. Moreover, the different in physiography of the area, or participation in the project determines also the difference in perception. The degree of popular participation on self sufficient reforestation or reforestation project is high. Popular participation is varied to either physiography condition or among participant of reforestation project. Participation of participant of reforestation project is higher than participation of self sufficient group.Â  The difference in the involvement of every reforestation of ativities (planning, implementation, and the use of out come) isÂ  a direct consequence of the different in physical as well as socio â economic condition of the community. Physical constraints of up land area, and low level of socio â economic condition, have stimulated popular participation on reforestation. In addition, the level of popular participation is very much influenced by knowledge on reforestation and perception on reforestation. This means that, the higher the knowledge of farmer on implementation and utilization of reforestation and the higher the farmer perception on reforestation programme, then the higher the level of farmer participation on reforestation in eah different physiography.